(untitled) (Khairulummah, 2025)
This research paper presents a comparative study of the methodological approaches of two eminent classical Qur’anic exegetes: al-Zamakhsharī (d. 538 AH), the author of al-Kashshāf, and al-Bayḍāwī (d. 685 AH), the author of Anwār al-Tanzīl wa Asrār al-Taʾwīl. Al-Zamakhsharī’s exegesis is distinguished by its Muʿtazilite theological orientation, its deep engagement with Arabic rhetoric (balāghah) and linguistics, and its rational interpretation of Qur’anic verses. In contrast, al-Bayḍāwī drew extensively from al-Zamakhsharī’s linguistic and rhetorical insights but revised or moderated Muʿtazilite theological positions in line with Ashʿarī principles, thereby offering a more balanced theological framework. The study analyzes both exegetes’ methodologies through several dimensions: principles of tafsīr, theological tendencies, interpretation of verses concerning divine attributes, use of taʾwīl, rhetorical style, linguistic analysis, and the balance between reason (ʿaql) and revelation (naql). The comparative analysis reveals that while al-Zamakhsharī embedded Muʿtazilite doctrines within his exegesis, al-Bayḍāwī systematically refined these interpretations, producing a tafsīr that became a standard reference for later Sunni exegetes. This research highlights the intellectual interplay between Muʿtazilite and Ashʿarī traditions in classical tafsīr and sheds light on the evolution of Qur’anic hermeneutics in Islamic thought.